2020
DOI: 10.31344/ijhhs.v4i2.179
|View full text |Cite
|
Sign up to set email alerts
|

Prevention is Better than Cure: Antibiotic Resistance and Management of Infectious Diseases

Abstract: not availableInternational Journal of Human and Health Sciences Vol. 04 No. 02 April’20 Page : 75-78

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A study form Tehran, reported that from the 99 MRSA isolates and the Susceptibility of MRSA isolates to linezolid and tigecycline suggests that these drugs may be have an important role in the treatment of infections caused by these multiresistant pathogens 8 . According to the Indian literature, it seems the impact of multidrug resistant MRSA is increasing over time; for example, 23.2% was reported by Manjula et al, (2007) Globally AMR is identified as the one of top public health for treating infectious diseases.9 One US study revealed that methicillin-resistant Staphylococcus aureus (MRSA) alone is more powerful to increase mortality level among peoples of the USA than emphysema, HIV/AIDS, Parkinson's disease and homicide combined 12 . Currently, the situation AMR is horrifying as almost all available antibiotics or antimicrobials for clinical use are resistant.…”
Section: Discussionmentioning
confidence: 99%
“…A study form Tehran, reported that from the 99 MRSA isolates and the Susceptibility of MRSA isolates to linezolid and tigecycline suggests that these drugs may be have an important role in the treatment of infections caused by these multiresistant pathogens 8 . According to the Indian literature, it seems the impact of multidrug resistant MRSA is increasing over time; for example, 23.2% was reported by Manjula et al, (2007) Globally AMR is identified as the one of top public health for treating infectious diseases.9 One US study revealed that methicillin-resistant Staphylococcus aureus (MRSA) alone is more powerful to increase mortality level among peoples of the USA than emphysema, HIV/AIDS, Parkinson's disease and homicide combined 12 . Currently, the situation AMR is horrifying as almost all available antibiotics or antimicrobials for clinical use are resistant.…”
Section: Discussionmentioning
confidence: 99%
“…As cited from Haque 2020, antibiotic resistance conditions will get worse because almost no new antibiotics will soon appear on the market to fight antibiotic resistance. 6 Adequate therapy is required to prevent the onset of complications of acute rhinosinusitis into chronic rhinosinusitis. Where surgery is the only treatment to treat chronic rhinosinusitis and other complications that occur when an acute infection is not treated properly.…”
Section: Introductionmentioning
confidence: 99%